2023
DOI: 10.3390/insects14020117
|View full text |Cite
|
Sign up to set email alerts
|

Invasion Genetics of the Horse-Chestnut Leaf Miner, Cameraria ohridella (Lepidoptera: Gracillariidae), in European Russia: A Case of Successful Involvement of Citizen Science in Studying an Alien Insect Pest

Abstract: Based on the intensive monitoring conducted by our team and volunteers in 2021, the secondary range of an alien horse-chestnut leaf miner, Cameraria ohridella Deschka & Dimić, 1986 (Lepidoptera: Gracillariidae), was specified in European Russia. This invasive pest was confirmed in 24 out of 58 administrative regions of Russia, which it has occupied for approximately 16 years. Analysis of the COI mtDNA gene sequenced in 201 specimens collected in 21 regions of the European part of Russia indicates the occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…In Belarus, since 2021, the species has been observed on silver maple Acer saccharinum [24]. In the southern region of Russia, a miner species was recorded on Acer pseudoplatanus L. [18], other plants were not noted as host for miner larvae before the author's research.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Belarus, since 2021, the species has been observed on silver maple Acer saccharinum [24]. In the southern region of Russia, a miner species was recorded on Acer pseudoplatanus L. [18], other plants were not noted as host for miner larvae before the author's research.…”
Section: Introductionmentioning
confidence: 95%
“…A study of the chestnut miner haplotypes of the European part of the Russian Federation and the Volga region [18] showed their low diversity in the secondary species distribution compared to the natural species distribution in Western Europe. It was found that only two of the 44 known C. ohridella haplotypes (8% of all known haplotypes) have an "invasive" trait, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, this species is resistant to such pests as the chestnut leafmining moth or the Ohrid miner Cameraria ohridella Deschka et Dimic (Lepidoptera, Gracillariidae, Lithocol letinae) [2]. Cameraria ohridella Deschka et Dimic was first discovered and described in Macedonia [3,4], and eventually spread almost everywhere in Europe [5][6][7]. On the territory of Russia, this phytophage was first officially registered in 2003 in the Kaliningrad region [8], and in 2005 phytophage mines were found on A. hippocastanum trees in the arboretum of the Main Botanical Garden in Moscow, where, most likely, the phytophage came with planting material imported from Europe [9].…”
Section: Introductionmentioning
confidence: 99%
“…Инвазионные виды насекомых распространяются с посадочным материалом (в большинстве своем -с крупномерными саженцами), с транспортом, с грузами нерастительного происхождения, самостоятельными перелётами и при помощи ветра [7]. Юг европейской части России стал в последние десятилетия реципиентом для множества новых видов вредителей растений, многие из которых нанесли существенный ущерб [3,6,7,8,17,18,20,25,26,27,31]. Основной удар принял на себя Краснодарский край, откуда происходит дальнейшее распространение инвайдеров.…”
unclassified